Perception of emergency medicine by consultants and specialist registrars from other hospital specialties. Issue 10 (22nd September 2009) - Reid, S; Stephenson, D; Bowden, L
Abstract : Background: This is the first study to consider feedback on the specialty of emergency medicine (EM) given by other hospital specialties. Method: A questionnaire was sent to 100 randomly selected consultants and specialist registrars from other specialties in a district general hospital in Northern England. The response rate was 67%. Results: 80% of respondents felt that the official term for the specialty should be "accident and emergency medicine". Resuscitation and major trauma were given the highest importance scores (>9/10) when evaluating the purpose of EM and minor injuries were given an intermediate importance score (6.5/10). Respondents advocated "rapid rule out" of acute medical problems by the emergency department (75%) and "any trained individual" carrying out ultrasound (72%) or stroke thrombolysis (59%) in the emergency department. Rapid sequence induction of anaesthesia exclusively by emergency physicians was unpopular (3%). Respondents were least satisfied with the study department's documentation, availability of senior staff 24 h/day and the availability of equipment and drugs. Polyclinics and closure of smaller emergency department were unpopular future proposals, while 70% advocated a revival of traditional out-of-hours general practice services. Conclusion: The perceived purpose, strengths and weaknesses of EM provide a focus for training and development, while opinion on new practices indicates areas where resistance to change may be met. The results can contribute to decision-making for emergency departments and for EM as it strives to adapt to its role in the modern NHS. Further similar studies are planned on a wider scale.